2017
DOI: 10.3390/s17112445
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia Evaluation in Wearable ECG Devices

Abstract: This study evaluates four databases from PhysioNet: The American Heart Association database (AHADB), Creighton University Ventricular Tachyarrhythmia database (CUDB), MIT-BIH Arrhythmia database (MITDB), and MIT-BIH Noise Stress Test database (NSTDB). The ANSI/AAMI EC57:2012 is used for the evaluation of the algorithms for the supraventricular ectopic beat (SVEB), ventricular ectopic beat (VEB), atrial fibrillation (AF), and ventricular fibrillation (VF) via the evaluation of the sensitivity, positive predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 47 publications
(55 reference statements)
1
26
0
Order By: Relevance
“…Works in short-term monitoring (duration of some minutes) and new public databases [ 50 ] can be found, as the intelligent heart-monitoring public cryptosystem, which involves a patient-worn ECG sensor and a remote monitoring station, using PT and classification trees as heartbeat detection and classification algorithms, respectively. More advanced methods, such as sample entropy, fast Fourier transform, and ANN, were recently selected for the integrated detection algorithms [ 21 ], in order to validate an arrhythmia detection method for supra and ventricular ectopic beats and atrial/ventricular fibrillation, when using the ANSI/AAMI EC57:2012 standard. Lossy methods, which traditionally were avoided in this setting, have been successfully revisited [ 18 ], and different compression methods based on the compression ratio and percentage root-mean-squared difference were proposed and advantageously benchmarked, including in terms of the accuracy of R-wave detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Works in short-term monitoring (duration of some minutes) and new public databases [ 50 ] can be found, as the intelligent heart-monitoring public cryptosystem, which involves a patient-worn ECG sensor and a remote monitoring station, using PT and classification trees as heartbeat detection and classification algorithms, respectively. More advanced methods, such as sample entropy, fast Fourier transform, and ANN, were recently selected for the integrated detection algorithms [ 21 ], in order to validate an arrhythmia detection method for supra and ventricular ectopic beats and atrial/ventricular fibrillation, when using the ANSI/AAMI EC57:2012 standard. Lossy methods, which traditionally were avoided in this setting, have been successfully revisited [ 18 ], and different compression methods based on the compression ratio and percentage root-mean-squared difference were proposed and advantageously benchmarked, including in terms of the accuracy of R-wave detection.…”
Section: Discussionmentioning
confidence: 99%
“…Noise data were made using physically active volunteers with standard ECG recorders, leads, and electrodes, and then adding it to the recordings from the MIT–BIH [ 19 , 20 ]. We selected these data for the wide use of its noise components (e.g., see [ 21 ]). LTSTDB.…”
Section: Databasesmentioning
confidence: 99%
“…Experimental results in the MIT-BIH database and in the actual patient showed that the EMD method has little effects only on the ECG characteristic features. The EMD method was also used in [22] in combination with the discrete wavelet transform (DWT) to detect R-peaks and QRS complex. The Probabilistic neural network (PNN) and radial basis function neural network (RBF-NN) were used to recognize the arrhythmia beats.…”
Section: A Short Review Of Methods For Breathing Effects Reduction Fomentioning
confidence: 99%
“…Artificial intelligence (AI) has been widely administered in considerable applications. It has been utilized for medical use such as arrhythmia problems [1,2], anesthesia [3,4] and blood pressure estimation [5]. Moreover, the AI also has been applied to energy systems [6][7][8], electromagnetic field [9] and shape optimization to increase the aerodynamics of the unmanned aerial vehicle [10].…”
Section: Introductionmentioning
confidence: 99%